Association of Body Mass Index with In-Hospital Left Ventricular Failure after Percutaneous Coronary Interventions - Siddiqui, Mohammad Khalilur Rahman; Karmakar, Pradip Kumar; Nabi, Shaila; Hossain, Mohammad Anowar; Faroque, Shahid Mohammad Omar; Khuda, Chowdhury Md Kudrat E; Karmaker, Pranob; Datta, Ratan Kumar; Ahsan, Mohammad Morshedul; Khan, Md Monir Hossain (Bangladesh Heart Journal, 2018)
Background: Obesity is an independent cardiovascular risk factor. The most common anthropometric measurement used to quantify obesity is body mass index (BMI). Percutaneous coronary intervention (PCI) is associated with various types of complications. The relationship between BMI and in-hospital complications particularly left ventricular failure (LVF) after PCI has not been thoroughly investigated, especially in Bangladesh. Methods: This cross sectional observational study was conducted at National Institute of Cardiovascular Diseases, on total 100 patients who underwent PCI with two equally divided groups on the basis of BMI of Asian ethnicity: Group I (BMI < 23 kg/m2) and Group II (BMI e” 23.0 kg/m2). In-hospital LVF after PCI were observed and recorded. Results: The mean BMI of study population was 23.9 ± 1.9 kg/m2. The sum of occurrence of adverse in-hospital outcomes was 14.0%. Complications were significantly (p < 0.01) higher in Group I than Group II. Among all adverse in-hospital outcomes, only acute left ventricular failure was found to be statistically significant between groups (p < 0.01). The difference of mean duration of hospital stay after PCI was higher in Group-I which was statistically significant (p < 0.01). Diabetes mellitus and dyslipidemia were found to be the independent predictors for developing adverse inhospital outcome (OR= 1.68 and 1.46; 95% CI = 1.25 – 2.24 and 1.16 – 1.83; p = 0.018 and 0.040, respectively). BMI was inversely associated with in-hospital outcomes after PCI (OR = 0.95; 95% CI = 0.91 – 0.98; p = 0.007). Conclusion: BMI is inversely associated with in-hospital LVF after PCI. The underweight and normal weight people are at greater risk to experience in-hospital LVF than overweight and obese people following PCI. Bangladesh Heart Journal 2018; 33(1) : 39-46